Evaluation of Different Dyspnea Scales in Smokers with Preserved FEV1/FVC Ratio - Besim Morina; Blerina Dervisholli; Mark Ross; Burim Neziri (International Journal of Biomedicine)
Background: This study evaluated the relationships between two dyspnea scales (Modified Borg Scale [MBS] and modified Medical Research Council dyspnea scale [mMRCds]) and clinical characteristics of smokers with preserved FEV1/FVC ratio. It also assessed their ability to differentiate symptomatic (CAT score ≥10) from asymptomatic smokers (CAT score <10). Methods and Results: Sixty-one smokers (FEV1: 98.69±15.83% of predicted, age: 29–77 years) were included in this study. Dyspnea intensity was assessed using MBS and mMRCds, and correlations were examined between these scales and pulmonary function tests, quality of life (QoL) indices, and physical parameters. ROC analysis determined cutoff values for dyspnea scales. MBS (1.29±1.16) and mMRCds (0.61±0.92) scores were higher in symptomatic smokers. Both scales significantly correlated with 6-minute walk distance (MBS: rs=-0.519; mMRCds: rs=-0.699; P<0.001 in both cases) and QoL measures (CAT, SGRQ). Spirometry parameters showed significant correlations with both scales. ROC analysis demonstrated strong discriminatory ability for both mMRCds and MBS between symptomatic and asymptomatic groups. Conclusion: mMRCds and MBS effectively assess dyspnea in smokers with preserved FEV1/FVC ratio, correlating with clinical and functional outcomes and distinguishing between symptomatic and asymptomatic individuals.